mary120

40 Reputation

One Badge

0 years, 322 days

MaplePrimes Activity


These are questions asked by mary120

Hi,

How do I solve numerically this set of equations with the following ICs to plot U1(x), phi(x),diff(phi(x),x) versus x:

diff(U1(x),x)=-diff(phi(x),x)/(U1(x)-T/U1(x));
diff(phi(x),x$2)=(1+A1*phi(x)+A2*phi(x)**(3/2)+A3*phi(x)**2)-(M1/U1(x));
where

A1:=(2*k-1)/(2*k-3);
A2:=8*sqrt(2/pi)*(beta-1)*k*Gamma(k)/(3*Gamma(k-0.5)*(2*k-3)**(3/2));
A3:=(4*k**2-1)/(2*(2*k-3)**2);
M1=0.1+sqrt(T+(1/A1));
(Gamma is gamma function)

assume, for example, T=0.1, pi=3.14, beta=0.6, k=3.5

ICs:

U1(x=0)=M1, phi(x=0)=0, diff(phi(x=0),x)=0.001.

Thanks.

Hi,

Consider the following planar dynamical system(PDS) with parameters r, p1, s, n:
a:=(r+1)*(1+p1*s)/(2*(1-P1))-1/(n^2);
b:=(r+1)*(3-r)*(1-p1*s^2)/(8*(1-p1))-3/(2*n^4);
c:=(r+1)*(3-r)*(5-3*r)*(1+p1*s^3)/(48*(1-p1))-5/(2*n^6);
 

 

 

Considering the follwoing expr:

A(x):=mue+(mun/gama)+(u0^2)-mud*x-mue*exp(x)-(mun/gama)*exp(gama*x)-(u0^2)*(1-2*x/u0^2)^(1/2);

where 

mue:=1/(1+alpha+beta);
mun:=alpha/(1+alpha+beta);
mud:=beta/(1+alpha+beta);
u0:=(mue+mun*gama)^(-1/2);
 and assuming the values of alpha and beta lie between 0.1..0.6 and gama=15 ro 20.

How do I determine those values of (alpha,beta,gama) satisfying conditions [(3), (4)], [(3), (5)] or [(3),(6)]?

conditions:

A(x[m] <> 0) = 0:

where x_m is an extreme point of A(x) (other than x=0),

d*A(x)/dx, x = x[m] < 0:

d*A(x)/dx, x = x[m] > 0:

d*A(x)/dx, x = x[m] = 0:

Hi,
How do I simplify the following polynomial:

 -(729 beta (1/2 (-1/9 (-5/27 beta-1/9) lambda^6-1/9 (1/9 beta^2 TT+(10/9 TE+2/3 TT) beta-1/9 TE) lambda^4+5/27 (2/5 TT (3/2 TT+TE) beta+TE (TE-2/5 TT)) beta lambda^2-1/9 TE beta^2 TT (-TT+TE)) p1(m,t)^2+(beta TT-1/3 lambda^2)^2 (-1/3 lambda^2+TE)^3 ((p2(m,t))/(lambda^2-3 TE)+3/2 ((lambda^2+TE) p1(m,t)^2)/((lambda^2-3 TE)^3))))/((3 beta TT-lambda^2)^3 (3 TE-lambda^2)^2),

as follows:

-3*beta*p2(m,t)/(lambda^2-3*beta*TT)+3*beta^2*(5*lambda^2-3*beta*TT)*p1(m,t)^2/(2*(lambda^2-3*beta*TT)^3)
?

How can I transform the following differential equation from (x,t) to (X,T) coordinate, where, for example, X=x-alpha*t, T=beta*t (alpha and beta are constant)

diff(z, t)+(diff(R, x))*L+A*(diff(L, x))+diff(k, x, x)-(diff(k, t, t)) = 0

Thanks.

1 2 Page 1 of 2